2020
DOI: 10.15517/rbt.v68i1.37652
|View full text |Cite
|
Sign up to set email alerts
|

Variation of benthic macroinvertebrate communities in streams of three landscapes of South Brazilian grasslands

Abstract: Introduction: Aquatic ecosystems in southern Brazil are presently under great environmental pressure. Changes in land use result in negative impacts on the ecosystem, affecting the functioning of stream communities. Objective: To compare the benthic macroinvertebrate community richness, abundances and compositions in streams of three South Brazilian grassland landscapes and correlate community patterns with environmental and spatial variables. Methods: Fifteen streams along riparian forests were selected in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…The indirect effects of land use on changes in environmental in-stream characteristics are most often represented by the shared explanation of variation between land use and environmental factors. For example, (Galeti et al, 2020) showed that intensive agriculture might alter the physicochemical characteristics of the water and potentially impair the ecosystem (Wu, 2008) (Wu, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The indirect effects of land use on changes in environmental in-stream characteristics are most often represented by the shared explanation of variation between land use and environmental factors. For example, (Galeti et al, 2020) showed that intensive agriculture might alter the physicochemical characteristics of the water and potentially impair the ecosystem (Wu, 2008) (Wu, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Among these environments, highland grasslands of subtropical South America harbor high endemism (Barros et al, 2015). However, despite their high endemism, highland grasslands are threatened by high levels of habitat fragmentation and loss in southern Brazil (Barros et al, 2015;Iganci et al, 2011), where more than 50 % of natural grasslands have already been converted into distinct human land uses over last two decades (Magalhaes et al, 2016;Galeti et al, 2020). In this way, examination of the patterns of aquatic macroinvertebrate community composition in relation to environmental conditions and dispersal capacity by means of α and β diversities may be an important tool for evaluating the impacts of anthropogenic land uses on subtropical highland grasslands and for proposing conservation plans (Doretto et al, 2021;Mendes et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, macroinvertebrates are a well-studied group in subtropical steams, with the diversity of the group being (i) negatively affected by anthropogenic land use (Barbola et al, 2011;Galeti et al, 2020;Tonello et al, 2021); (ii) pos-itively affected by oxygen concentration and high granulometry heterogeneity (Baptista et al, 2014); (iii) influenced by inter-annual temporal factors (Hepp et al, 2021); (iv) negatively affected by the input of leaf litter chemical compounds resulting from anthropogenic land uses (Loureiro et al, 2018(Loureiro et al, , 2021; and (v) highly similar between neighboring areas (i.e., local scale; Hepp & Melo, 2013;Hepp et al, 2021). It is noteworthy that most of these studies focused on forest streams and only a few studied the macroinvertebrate fauna of subtropical grasslands (Baptista et al, 2014;Hepp & Melo, 2013;Hepp et al, 2021;Loureiro et al, 2018Loureiro et al, , 2021Tonello et al, 2021), few of which were in highland grasslands (Galeti et al, 2020;, Montilla et al, 2022Principe et al, 2015). Similarly, subtropical highland grasslands have been understudied compared to tropical highland grasslands (Callisto et al, 2016(Callisto et al, , 2021Castro et al, 2019).…”
Section: Introductionmentioning
confidence: 99%